Distribution of ABO and Rh (D) blood group and allele frequency in North-East India: a systematic review - Gupta, Muskan; Sharma, Mukunda Anuj; Singh, Bisu (International Journal of Research in Medical Sciences, 2025)
Despite several reviews on ABO and Rh (D) blood group frequencies across different regions of India, a comprehensive analysis from North-Eastern states of India is lacking. This systematic review analysed the distribution and allelic frequencies of ABO and Rh (D) antigens among the states and ethnic groups in North East India. Databases including PubMed, Google Scholar, Web of Science, Science Direct and the library web portal of Sikkim University were searched for articles published between 1958 and 2024. After screening for titles, abstracts, and full texts, 24 original research articles were included for review. The allelic frequency of blood antigens was calculated using Hardy-Weinberg equilibrium model. Studies from seven states of North East India, including a total of 40,513 individuals’ ABO data, were analyzed. Blood group O (36.07%) was found to be most prevalent followed by A (30.72%), B (24.66%), and AB (8.55%). Blood group O was dominant in Arunachal Pradesh, Assam, Manipur, Sikkim and Nagaland; A in Meghalaya; and B in Tripura. The allelic frequencies for IA (p), IB(q) and i(r) were found to be 0.22, 0.18 and 0.60 respectively. A total of 98% individuals were Rh(D) positive, while 2% were Rh(D) negative. A notable variation was observed for ABO frequency among the various ethnic populations of North-East India. Even though variations were observed in blood group frequency among the ethnic groups and states of North East India, overall frequency was found to be in the order: O>A>B>AB.